IMPACT OF SUPERVISION, SCHOOL CLIMATE AND COMPENSATION ON TEACHER PROFESSIONALISM - Abdul Latip; Ellin Herlina; Irawan Budiutomo (International Journal of Management, Economic, Business and Accounting, 2022)
Purpose of the study — This research purpose is to analyze how are the supervision, school atmosphere and teachers professionalism at MTs ANNUR Karangjunti Losari Brebes. Research method—It is quantitative research with regression. This research use quantitative approach to look causality from a few factors which affect to teachers professionalism. Population in this research were teachers at MTs ANNUR Karangjunti Losari Brebes with totals of 40 teachers. Data collected with quessionaire and research documents. Then, data is tested by validity and reliability. Result of the research showed that, supervision, school athmosphere and compentation affected to teacher professionalism simultaneously. Result— The multiple determination coefficient in this research use the adjusted R Square value, because the independent variables in this research is more than 2 in affect’s estimation from two independent variable research by find that adjusted R square value about 0,656, its means that affect X1, X2 and X3 variables are 65,6% to the changes of Y or independent variable affect (supervision, school athmosphere, and compentation) to dependent variable (professionalism) is about 65,6% while remaining is 34,4% cause of other variable are exclude in this framework. Conclusion— Hope that the educational institution leader to pay more attention to the teachers and the educationals staffs in order to become professional teachers. As well to increase supervision and school atmosphere and give attention to fairer compentation based on their abilities or competencies in teaching and learning activities.